Distribuição do espadarte, xiphias gladius (linnaeus, 1758) capturado pela frota brasileira e potencial de utilização de estratégias de manejo espacial como instrumento de gestão - Lima, Antõnia Duciene Feitosa (Universidade Federal Rural do Semi-Árido, 2020)
Pelagic industrial fisheries are the subject of great controversy, hovering between the essential supply of food and its impact. Although statistics show a decline in the catch of some species, this fishing is still seen as an alternative to exploiting fishery resources. Thus, studies that relate the population structure of the captured species with operational and environmental variables, contribute directly to the management of these resources. Following this line, the present study aimed to contribute with technical-scientific knowledge about the fishing and ecology of swordfish (Xiphias gladius, Linnaeus, 1758), coming from the Brazilian longline fleets, operating in the West Atlantic, in the period from 2010 to 2016, in order to promote the exploration of this important oceanic fishery resource, based on the evaluation of the potential use of spatial management strategies as a management tool. The methodology used to evaluate the relationship of explanatory variables and response was the Mixed Generalized Additive Model (GAMMs) method. The use of this model proved to be a very useful statistical tool, indicating that all tested variables of the final model were highly significant. The results indicate that the swordfish generally occurs between latitudes from 10ºN to 30ºS and between longitudes of 20º to 50ºW. It preferably follows the temperature range below 25 ° C, at depths below 60 meters, with an increasing trend below 20 meters. For lunar illumination index, it presented better tendencies to intermediate illumination intensity, predominating in the increasing phase. Regarding the effect of chlorophyll, it was less significant when compared to the other variables tested, with the opposite relationship between the effect and the amount of chlorophyll. The results generated in this study on operational and environmental interactions with swordfish CPUE suggest areas and times that can be used by fishing fleets and government institutions as a starting point for swordfish management strategies.
Keywords: Pesca industrial; Modelos Aditivos Generalizados Mistos; Variáveis ambientais; Industrial fishing; Mixed Generalized Additive Models; Environmental variables; CIENCIAS BIOLOGICAS::ECOLOGIA